ACCURACY OF DEM-BASED TOPOGRAPHIC DATA IN FLOOD INUNDATION MODELLING: A CASE OF WAMI RIVER, TANZANIA - Ndomba, Preksedis M (Tanzania Journal of Engineering and Technology, 2017)
The objective of this paper is to evaluate and further comment on the accuracy of the DEM- based topographic data as input in flood modelling. Recent studies have indicated that hydraulic parameters of the modified cross sections based on high resolution DEM are geometrically and hydraulically similar to the measured ones. In the current study hydraulic modelling was intended to guide a development project whereby a floodplain protection embankment is contemplated. Therefore, accuracy in terms of positioning/alignment of natural features such as river banks and heights/elevations was imperative to attain. In order to achieve these, accuracy of various topographic data sources were qualitatively and/or quantitatively analysed before and after hydraulic modelling. As the study river reach is ungauged, the hydraulic model was verified and validated with field observations, readily available information and professional judgement. Based on error analysis, it was found that uncalibrated 90-m resolution STRM DEM-based topographic data are biased, i.e., 80% of the error mass is negative. The error increases with elevation. The final input to the hydraulic model was a composite/hybrid DEM derived after merging geometric data from four representative field-measured cross sections, a 2-m interval contour map covering part of the river valley, and calibrated 90-m resolution DEM. Although, calibration improves the data, it does not remove completely the inherent bias. Further to DEM calibration, it was therefore recommended to include an elevation uncertainty value of -0.5 m, as derived from topographic analysis, into simulated water surface profiles elevations. The hydraulic model satisfactorily simulated flood inundation extent after considering the elevation uncertainty. In order to improve the findings further studies should use adequate measured cross sections and DEM of higher resolutions.